Penggunaan Voice-Over untuk Melancarkan Kegiatan Pengajian di Majelis Ta’lim Syibil Barokah - Oktafiandini, Nabila Safitri Dwi; Wahidah, Idah (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2022)
Recitation is one of the routine activities that are usually carried out by Sukatani residents. However, since the COVID-19 pandemic, recitation activities cannot be carried out as usual because it will cause a crowd. The purpose of this KKN-DR activity is to help residents of Sukatani so that they can continue to carry out recitation activities even though they are at home. The method used is SISDAMAS or community empowerment. With this method, there are 3 cycles, namely social reflection, participatory planning plus program synergy, and program implementation and evaluation. The use of voice-over applications is one solution to the existing problems. For activities at the mosque, residents still come according to the schedule that has been made. If the recitation activities are in progress, residents can still attend the recitation even though they are at home. One indicator of the success of using the Voice-over application is that it can be seen from the recitation attendance list. There is an increase in the number of people attending the recitation